2021
DOI: 10.1097/ico.0000000000002872
|View full text |Cite
|
Sign up to set email alerts
|

Graft Thickness at 6 Months Postoperatively Predicts Long-Term Visual Acuity Outcomes of Descemet Stripping Automated Endothelial Keratoplasty for Fuchs Dystrophy and Moderate Phakic Bullous Keratopathy: A Cohort Study

Abstract: Purpose: It remains unclear whether preoperative central graft thickness (CGT) contributes to visual outcomes of Descemet stripping automated endothelial keratoplasty (DSAEK). This retrospective cohort study examined the ability of preoperative and postoperative CGT to predict 12-month best spectacle-corrected visual acuity (BSCVA) after DSAEK for Fuchs endothelial corneal dystrophy/moderate pseudophakic bullous keratopathy/second graft.Methods: All consecutive patients who underwent DSAEK in 2015 to 2018 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This may reflect, at least in part, differences between the study populations in terms of surgical practice, variable measurement, postoperative timepoint, and study/statistical design. It is also possible that significantly-associated pre/perioperative variables relate only indirectly to the fundamental endothelial cell variable(s) that ultimately shape(s) the postoperative density and function of these cells [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect, at least in part, differences between the study populations in terms of surgical practice, variable measurement, postoperative timepoint, and study/statistical design. It is also possible that significantly-associated pre/perioperative variables relate only indirectly to the fundamental endothelial cell variable(s) that ultimately shape(s) the postoperative density and function of these cells [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggested that the variable CGT-BSCVA relationships reported in the literature may reflect inaccuracies or variation in the preoperative CGT measurements due to various factors (e.g. graft culture duration) that blur the relationship between CGT and visual acuity; these factors disappear after surgery, allowing the intrinsic relationship between CGT and BSCVA to emerge [30]. Our explorations in the present study suggested that a similar phenomenon may be operating in the relationship between CCT and BSCVA in DMEK: we found that unlike preoperative CCT, postoperative CCT did correlate significantly with final BSCVA.…”
Section: Correlation Between Postoperative Cct and 12-month Bscvamentioning
confidence: 99%
“…Another possibility is suggested by our earlier study on the relationship between central graft thickness (CGT) and final BSCVA after DSAEK [30]. Whether thinning DSAEK grafts actually improves visual outcomes has been a vexed question in the literature, with some studies [31][32][33][34][35][36] but not others [37][38][39][40][41][42][43][44] finding an effect.…”
Section: Correlation Between Postoperative Cct and 12-month Bscvamentioning
confidence: 99%